Method of sampling chorionic villi in first trimester of pregnancy under guidance of real time ultrasound. Issue 6377 (14th May 1983) - Ward, R H; Modell, B; Petrou, M; Karagözlu, F; Douratsos, E
Abstract : Samples of chorionic villi were obtained in the first trimester by aspiration using a cannula passed transcervically under the guidance of real time ultrasound. In initial studies in 47 anaesthetised patients immediately before therapeutic abortion a method was developed giving a success rate of 89%. In 10 patients successful sampling was performed as an outpatient procedure without anaesthesia. In all, seven diagnostic procedures were undertaken and four of the five unaffected pregnancies continued. The technique of chorionic villous sampling using real time ultrasound is simple to learn and yields material for biochemical analysis and chromosomal study without the need for tissue culture. The exact obstetric risk, however, remains to be defined.